Nexus between Inflation, Inflation Perceptions and Expectations† - NAM, MINHO (KDI Journal of Economic Policy, 2018)
We uncover a nexus between actual inflation, inflation perceptions and expectations in Korea through analyzing micro as well as aggregate data from the Consumer Survey. We document two novel findings. First, households’ subjective perceptions of inflation exert more impact on expectation formation than actual inflation. Second, inflation perceptions are broadly in line with the trajectory of the inflation trend. This is attributable to the fact that changes in actual inflation have been generated mainly by the consumption items whose price changes are perceived more sensitively as those items are frequently bought or have a larger share in household expenditures. Conducting a cross-country comparison, we find that information rigidity in expectation formation process and the nexus between perceptions and expectations of inflation prove to be stronger in Korea. Additionally, we reconfirm the existing finding that the scope of information utilized for forming inflation expectations is fairly circumscribed.